Cross talk of c-Jun N-terminal kinase and p38 map kinase modulate insulin and TNFα-stimulated VCAM-1 expression in rat aorta endothelial cells - Gregory B. Pott; Mark Tsurudome; Jamie Bui; Chelsea Gardner; Marc Lee Goalstone (International Association of Physical Chemists (IAPC), 2016)
VCAM-1 cell surface expression was determined by flow cytometry in rat aorta endothelial cells stimulated with insulin and/or Tumor Necrosis Factor-a in the absence or presence of short-hairpin RNA inhibitors of c-Jun N-terminal Kinase (JNK) and p38 MAP Kinase. Cells transfected with insulin alone exhibited moderate increases in cell surface VCAM-1 expression, whereas cells stimulated with TNFα alone or in combination with insulin, exhibited a significant (P, 0.05) increase in VCAM-1 surface expression. Cells transfected with shJNK alone showed increased VCAM-1 expression at the cell surface as compared to mock-transfected positive controls. In contrast, cells transfected with shp38 exhibited significant decreased insulin-stimulated VCAM-1 expression at the cell surface, but only moderate decreased VCAM-1 expression in cells stimulated by TNFα alone in combination with insulin. Interestingly, in cells first tranfected with shJNK and then shp38, VCAM-1 expression appeared to increase in an additive fashion. In contrast, cells transfected with shp38 first then shJNK, VCAM-1 expression exhibited increased VCAM-1 expression even in the presence of shp38. One can conclude that JNK is a potent negative regulator of insulin- and TNFα-stimulated cell surface expression of VCAM-1, whereas p38 is mild positive regulator of insulin-, but not TNFα-stimulated VCAM-1 expression. JNK appears to be a more potent mediator of insulin- and TNFα-stimulated cells surface VCAM-1 expression than p38 MAP Kinase. Thus, it could be a therapeutic target for amelioration of inflammation-associated VCAM-1 expression and its sequelae of events that lead to atherosclerosis.